Instruments of educational inspection (I): field notebook - José Francisco Pérez Aguilar (ADIDE Federación, 2016)
The educational inspection formulates proposals, recommendations or, if appropriate, requirements management teams and teachers for their teaching and management work suits optimize or regulations. Before reaching those conclusions, inspectors should assess observations, readings and testimonies collected in their field notebooks constituting together with the report and the visit of instruments for the implementation of their acting techniques. In this article a number to study and analyze them as all three have enough to acquire such consideration identity begins. However, inspectors apply other resources for gathering information such as tables, forms, questionnaires or single notes. The analysis is performed on the field book aims addition to conceptualize and structure, file-based information technology and communication that aims to solve the dispersion of resources specified to prevent data loss and such facts.